Computational study of positron annihilation parameters for cation mono-vacancies and vacancy complexes in nitride semiconductor alloys. (20th August 2019) - Ishibashi, Shoji; Uedono, Akira; Kino, Hiori; Miyake, Takashi; Terakura, Kiyoyuki
Abstract: We calculate positron annihilation parameters, namely the S and W parameters from the Doppler broadening spectroscopy and the positron lifetime, for defect-free states as well as cation mono-vacancies and vacancy complexes in nitride semiconductor alloys Al0.5 Ga0.5 N, In0.5 Ga0.5 N and Al0.5 In0.5 N. The obtained distributions of these parameters differ from compound to compound. Especially, the S – W relation for In0.5 Ga0.5 N is very different from that for Al0.5 Ga0.5 N. For the cation mono-vacancies, introducing local structural parameters, their correlations with S, W and are investigated. The S and variations are well described with the size distributions of the vacancies while the W variation is related to the presence of localized d electrons. For the vacancy complexes as well as the cation mono-vacancies, multiple-linear-regression models to describe S, W and are successfully constructed using the local structural parameters as descriptors. The S – W and S – relations are also compared with those for AlN, GaN and InN.